Biotransformation of Monoterpenoids by Suspension Cultures ofLavandula angustifolia: Monoterpenoid biotransformation - Shams Ardekani, Mohammad Reza; ALinley, Peter; Harkiss, Keith J; Mohagheghzadeh, Abdolali; Gholami, Azra; Mosaddegh, Mahmood (Iranian Journal of Pharmaceutical Sciences, 2007)
Callus and suspension cultures of Lavandula angustifoliaMill. (Lamiaceae)were established and the effect of different culture media on growth rate wasinvestigated. Terpenoids added to suspension culture to investigate their biotrans-formation. All samples were analyzed by gas chromatography (GC) and GC-massspectroscopy (MS). Octan-1-ol, citronellol, linalool, borneol and geraniol werebiotransformed products of octanal, citronellal, linalyl acetate, bornyl acetate andgeranyl acetate, respectively. Citronellol, linalool, borneol, and menthol didn’tchange by L. angustifoliasuspension cultures. Blue pigment production by culturesof L. angustifoliawas also studied. Ester hydrolysis and oxidation were the main reactions which occurred in biotransformation process, which may be attributed tothe presence of related or bifunctional enzymes. This technique is a possible wayof the production of expensive or rare compounds from cheap and plentiful substrates.